Structural Basis of Design and Engineering for Advanced Plant Optogenetics. (January 2020) - Banerjee, Sudakshina; Mitra, Devrani
Abstract : In optogenetics, light-sensitive proteins are specifically expressed in target cells and light is used to precisely control the activity of these proteins at high spatiotemporal resolution. Optogenetics initially used naturally occurring photoreceptors to control neural circuits, but has expanded to include carefully designed and engineered photoreceptors. Several optogenetic constructs are based on plant photoreceptors, but their application to plant systems has been limited. Here, we present perspectives on the development of plant optogenetics, considering different levels of design complexity. We discuss how general principles of light-driven signal transduction can be coupled with approaches for engineering protein folding to develop novel optogenetic tools. Finally, we explore how the use of computation, networks, circular permutation, and directed evolution could enrich optogenetics. Highlights: Optogenetics uses light to stimulate cells that have been genetically modified to express light-sensitive proteins. Despite their potential, several experimental and computational approaches in optogenetics remain underutilized. Although most optogenetic systems were developed from plant photoreceptors, optogenetics has rarely been applied to plants.